Comparison of insulin-like growth factor-1 and sclerostin levels between premenopausal women with and without diabetes mellitus. Issue 5 (October 2021) - Sylvawani, Mahriani; Setyohadi, Bambang; Purnamasari, Dyah; Abdullah, Murdani; Kurniawan, Muhammed R.
الملخص : أهداف البحث: تقيم هذه الدراسة مستويات المصل لعامل النمو الشبيه بالأنسولين -١ وسكلروستين كعلامات لانخفاض تكوين العظام لدى النساء قبل انقطاع الطمث المصابات بداء السكري من النوع ٢. طرق البحث: تم إجراء دراسة مقطعية حيث تم قياس مستويات مصل عامل النمو الشبيه بالأنسولين -١ وسكلروستين في مصل ٤٠ امرأة قبل انقطاع الطمث مع أو بدون داء السكري باستخدام مقايسة الممتز المناعي المرتبط بالإنزيم. وتمت مقارنة مستويات عامل النمو الشبيه بالأنسولين -١ وسكلروستين بين المجموعات. النتائج: كان متوسط مستويات عامل النمو الشبيه بالأنسولين -١ في الدم ٤٠.٦٠نانوغرام / مل و٤٢.٧ نانوغرام / مل في المجموعات المصابة بالسكري وغير المصابة بالسكري، على التوالي مع عدم وجود فرق معنوي. كانت مستويات سكليروستين في المصل أعلى بكثير في مجموعة مرضى السكري مقارنة بالمجموعة غير المصابة بالسكري، ١٣٢.١ بيكوغرام / مل و٩٦.٠بيكوغرام / مل، على التوالي. الاستنتاجات: كانت مستويات سكليروستين أعلى بشكل ملحوظ في النساء في فترة ما قبل انقطاع الطمث المصابات بداء السكري مقارنة مع غير المصابات بداء السكري. نظرا لأن سكلروستين يؤثر على تمايز ونضج بانيات العظم، فقد يكون من المحتمل أن يكون سكلروستين المصل مفيدا كعلامة على انخفاض تكوين العظام لدى النساء المصابات بالسكري قبل انقطاع الطمث. Abstract: Objectives: This study assesses the serum levels of insulin-like growth factor-1 (IGF-1) and sclerostin as markers of decreased bone formation in premenopausal women with type 2 diabetes mellitus. Methods: A cross-sectional study was conducted to measure serum levels of IGF-1 and sclerostin in 40 premenopausal women with and without diabetes mellitus using an enzyme-linked immunosorbent assay. The levels of IGF-1 and sclerostin were compared between the groups using the Mann Whitney test and unpaired t-test, respectively. Results: The median IGF-1 serum levels were 40.60 ng/mL and 42.7 ng/mL in the diabetic and non-diabetic groups, respectively, with no significant difference. The serum levels of sclerostin were significantly higher in the diabetic group than in the non-diabetic group (132.1 pg/mL and 96.0 pg/mL, respectively; p  < 0.001). Conclusion: The levels of sclerostin were significantly higher in premenopausal women with diabetes mellitus than in the non-diabetic group. Since sclerostin influences the differentiation and maturation of osteoblasts, serum sclerostin might potentially be useful as a marker of decreased bone formation in premenopausal women with diabetes.